Clinical profile of neonates admitted with hypernatremia in NICU at tertiary hospital in Vadodara, Gujarat, India - Pandya, Nimisha; Mehta, Kedar G. (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal hypernatremia is less common but significant metabolic problem with acute morbidity as well as long term consequences. Many causative factors have been identified such as inadequate breastfeeding, hot weather with high evaporative losses , infections etc. It is important to identify, anticipate and correct the condition before it leads to damaging consequences. The objective of the present study was evaluation of clinical profile, renal parameters and causative factors associated with hypernatremia in exclusively breast-fed infants. Methods: A retrospective review of 30 new-borns less than 28 days of age admitted in GMERS General hospital for hypernatremia was conducted. The study group included inborn and out born admissions. Records were reviewed, feeding history, severity of hypernatremia and altered renal parameters were analysed. The study period was from April 2018to June2018i.e summer months. Results: Total NICU admissions were 303 during these months out of which 30 were diagnosed with hypernatremia completely and discharged. Mean age of presentation was 8.4 days. Sodium levels ranged from 146-179 mmol/l. Mild hypernatremia was most common (56.7%), followed by moderate hypernatremia in 40%. All neonates were on exclusive breast feeding. Majority of the affected neonates were term SGA followed by term AGA and preterm AGA. Renal parameters were altered in quarter of affected infants. Most common clinical feature noted was lethargy(70%), followed by fever(53.3%),significant weight loss ,jaundice and dehydration. 29 patients were successfully discharged on breast milk feeding. Conclusions: Hypernatremia though rare, is common in young infants in summer months. It is preventable and treatable condition. It is important to anticipate, identify and treat such patients at the earliest. Treating physicians and nursing staff should be more vigilant for establishment of breast feeding in low birth weight infants. Exclusive breast feeding for first six months of life should always be promoted.